Challenges and Innovations in Healthcare Fraud and Waste Detection Systems: A Systematic Review and Proposed Framework - Schneider, Gelson André; Korzenowski, André Luis (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS); 2025: Anais do XXV Simpósio Brasileiro de Computação Aplicada à SaúdeDO - 10.5753/sbcas.2025.7061, 2025)
Fraud and abuse in the healthcare sector cause considerable financial losses to public and private entities.This article conducted a systematic literature review to identify the challenges in fraud and waste detection systems. Ten articles were identified in the review that covered the IEEE, PubMed, Scopus, and Web of Science bases. Based on these studies, we developed a framework in which we categorized the works by anomaly point, contextual, and collective. We also identified the unsupervised learning techniques used and identified the following challenges dimensionality reduction, conceptual deviations caused by changes in fraudsters’ behavior to bypass audit systems, and the need for real-time detection support.